Computational assessment of wave stability against submerged permeable breakwaters: A hybrid finite element method approach - Tulus, .; Rahman, Md Mustafizur; Sutarman, .; Muhammad Romi, Syahputra; Marpaung, Tulus Joseph; Marpaung, Jonathan Liviera (International Information and Engineering Technology Association, 2023)
Wave propagation, a phenomenon involving the transfer of energy over time, is a significant area of study, particularly with respect to sea waves. Due to their unique geometrical properties and inhomogeneous minimum amplitude, sea waves pose distinct challenges for numerical solutions. This research focuses on the analysis of wave stability against various water velocities and breakwater distances from the coastline. The study employs a hybrid approach, utilizing the Finite Element Method (FEM) to determine the movement of fluid elements through a porous, submerged breakwater. The concept of permeability in breakwaters is integral to this analysis. Permeable breakwaters permit a certain proportion of seawater or wave water to pass through, while absorbing or reflecting the remaining component of the waves. Understanding the permeability of breakwaters can enhance the design effectiveness and efficiency, whilst providing insight into potential impacts on coastal ecosystems. The results of the study demonstrate that the distance of the breakwater from the incoming wave influences both the amplitude and speed of the wave. Specifically, a greater distance between the wave and the breakwater results in a decrease in wave height, thereby increasing the stability of the simulation. For example, the directional and speed components of the movement at [x, y, t] for the first amplitude [20, 2, 15] was found to be 0.12515m, the second amplitude [15, 2, 15] 0.13161m, and the third amplitude [10, 2, 15] 0.13097m. This demonstrates that the breakwater's distance significantly influences wave stability, an important factor to consider in future breakwater design and implementation.